2019
DOI: 10.1101/686550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of DNM3 and VAMP4 as genetic modifiers of LRRK2 Parkinson’s disease

Abstract: Abbreviations. PD = Parkinson's disease, LRRK2 = Leucine-rich repeat kinase 2, AAO = age at onset, DNM3 = Dynamin 3, KASP = 'Kompetitive' allele-specific polymerase chain reaction, MAF = minor allele frequency, GWAS = Genome-wide association study, SNP = single nucleotide polymorphism Abstract Objective: To assess the reported LRRK2 age-at-onset (AAO) modifier DNM3 rs2421947, and the proximate genome wide association signal VAMP4 rs11578699 on AAO of Parkinson's disease (PD), with rare (rs34637584; p.G2019S) o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Because AAO genetic modifiers have been nominated for LRRK2 + /PD + , effect sizes have been small and ethnicity/populations seem to play a role 11,15–18 . This study establishes a connection between environmental and lifestyle factors that adds to the complexity in LRRK2 + /PD + .…”
Section: Discussionmentioning
confidence: 75%
“…Because AAO genetic modifiers have been nominated for LRRK2 + /PD + , effect sizes have been small and ethnicity/populations seem to play a role 11,15–18 . This study establishes a connection between environmental and lifestyle factors that adds to the complexity in LRRK2 + /PD + .…”
Section: Discussionmentioning
confidence: 75%
“…Thirteen variants from seven genes passed our QC (rs4273468 from BST1; rs2421947 from DNM3; rs1564282 from GAK; rs1052553, rs242562, and rs2435207 from MAPT; rs823144 from PARK16; rs11931074, rs1372525, rs181489, rs2583988, and rs356219 from SNCA; rs11578699 from VAMP4). [19][20][21][22][23][24][25][26][27][28][29][30][31]33,34 Only four variants from three genes had P-values < 0.05: rs823144 from PARK16 in the penetrance model (P-value=0.01); rs1564282 from GAK in both the penetrance (P-value=0.03) and age-at-onset models (P-value=7.1E-03); rs2345207 (P-value=5.1E-04) and rs1052553 (P-value=0.02) from MAPT in the penetrance model. Unfortunately, since some individuals in our study may have also been included in the previous studies where these candidate genes were first reported, our findings do not represent independent replication.…”
Section: Discussionmentioning
confidence: 99%
“…33 This finding was not independently replicated, although it was still significant in a meta-analysis including the participants reported in the original finding. 24,34 Genome-wide association studies have successfully detected many disease genes/variants, including those associated with PD. However, to date, no GWAS for LRRK2 modifiers has been reported, probably due to limitations in sample size and corresponding statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent topic is penetrance or age of onset modifiers in carriers of LRRK2 and GBA damaging variants. Where for LRRK2 the GRS was shown to play a role in penetrance and age of onset [22,23] and for GBA besides the GRS affecting penetrance and age of onset variants in close proximity to CTSB and SNCA were affecting penetrance [24].…”
Section: Risk Scores Prediction Pathways Progression Modifiers Amentioning
confidence: 99%